Utilization of Patin Fish Bone Waste in Making Snack Bar - Fitria, Fitria; Marlina, Yessi (JURNAL PROTEKSI KESEHATAN, 2024)
Fish bone waste can be utilized as catfish bone meal for additional ingredients in making snack bars. This study aims to determine the level of consumer acceptance, as well as to determine the macro nutrients of snack bars with the addition of catfish bone meal. Product manufacturing begins with the manufacture of catfish bone flour and then making 4 snack bar formulations and followed by hedonic test / sensory test. Data were analyzed using the One Way Annova test with a significance level of 0.05 and if there was a significant difference, it was continued with the Duncan test. Calculation of nutritional value was carried out using the Proximate analysis method to determine the content of water, ash, protein, fat and carbohydrates using the SNI 01-2891-1992 method, and calcium analysis using the Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) method. The addition of catfish bone meal did not significantly affect the color, aroma, taste or texture attributes of snack bars (p>0.05). The selected product based on the results of hedonic and content tests is P2 (with the addition of 10 g catfish bone meal) with a slightly brownish beige color, sweet taste, has a distinctive aroma of snack bars with a slightly hard texture. The nutritional content of the selected product is 13.46% moisture content, 3.7% ash content, 20.45% protein, 17.89% fat, 19.95% carbohydrate and 628.52 mg/ 100 g calcium.